The Consequences of currency intervention in India - Ila Patnaik (Indian Council for Research on International Economic Relations (ICRIER), 2003)
Currency management in India has focused on delivering low levels of currency volatility. In earlier years, the implementation of the currency regime was enabled by the presence of capital controls. In recent years, India has made much progress towards capital account convertibility. This paper closely examines India's experience with the implementation of the currency regime in two episodes: 1993-95 and after 2002. We argue that the implementation of the existing currency regime now induces distorted monetary policy and fiscal costs. These costs of implementing the currency regime need to be factored into the choice of currency regime
Keywords: 330